Circular Maker Cities: Maker Space Typologies and Circular Urban Design - Reham Elwakil; Ingrid Schroder; Koen Steemers (Buildings, 2023)
Maker spaces can contribute significantly to the circular economy of cities; they demonstrate not only the economic potential of inner loop circularity, but also provide tangible evidence of spatial and social integration of production into the urban context. This paper presents findings from a typological analysis of 326 maker spaces in seven European cities, with a focus on selected exemplar case studies to reveal design characteristics, principles, and opportunities for circular city development. The research shows that circular economy principles of ‘reduce-reuse-recyle’ are aligned with maker spaces such as repair cafés, secondhand shops, and fab labs, but requires additional definition with respect to material flow and spaces for recycling to underpin circular making. In the context of cities, circularity is revealed by a spatial tightening of resource cycles that close the loops of product life cycles. Furthermore, urban maker spaces demonstrate social engagement and a relationship to local production that inherently includes maintenance, repair, reuse, and redistribution. This paper defines five maker typologies, presents exemplars of each from different urban contexts and posits hybrid design strategies for the transition to circular maker cities. Through the adoption of these findings into urban planning policy, it is possible accelerate circular urban production and close the sustainability gap between small-scale local and large-scale regional manufacturing.